(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Medico-legal issues are attracting the attention of public as well as media and complaints & lawsuits against doctors seem to be on rise. Hence knowledge about Medico Legal cases & issues is extremely important during practice of medicine. Therefore present study was carried out to assess the knowledge & awareness of medical students about medico legal cases. This study was done on 290 participants. Study shows that the, participants are more aware about the questions related to various clinical of medical legal cases & procedures but are less aware about the questions related to their handling & documentation. They are least aware about questions related to medical, laws, ethics & autopsy. Hence the knowledge regarding various medico-legal aspects needs to be updated from time to time. Mandatory casualty & mortuary posting for Interns under the Department of Forensic medicine is need of an hour.